Research Relevant Background Lesions and Conditions: Ferrets, Dogs, Swine, Sheep, and Goats. (13th March 2021) - Helke, Kristi L; Meyerholz, David K; Beck, Amanda P; Burrough, Eric R; Derscheid, Rachel J; Löhr, Christiane; McInnes, Elizabeth F; Scudamore, Cheryl L; Brayton, Cory F
Abstract: Animal models provide a valuable tool and resource for biomedical researchers as they investigate biological processes, disease pathogenesis, novel therapies, and toxicologic studies. Interpretation of animal model data requires knowledge not only of the processes/diseases being studied but also awareness of spontaneous conditions and background lesions in the model that can influence or even confound the study results. Species, breed/stock, sex, age, anatomy, physiology, diseases (noninfectious and infectious), and neoplastic processes are model features that can impact the results as well as study interpretation. Here, we review these features in several common laboratory animal species, including ferret, dog (beagle), pig, sheep, and goats.